Prinsip Akutanbilitas Dalam Kebijakan Pengelolaan Keuangan Daerah Berbasis Wajar Tanpa Pengecualian - R.A. Rini Anggraini; Iwan Rachmad Soetijono; Barlian Ary Ajiwijaya (Lembaga Pengembangan Kinerja Dosen, 2023)
Regional finance is a right and obligation. Rights are regional rights to seek regional revenue sources in the form of collecting regional taxes, regional levies or other sources of revenue in accordance with applicable laws and regulations. Meanwhile, the obligation is the obligation of the region to issue money in order to carry out all regional government affairs. In its implementation, the financial management carried out by each region is accountable to the Supreme Audit Board (BPK). Regions that are categorized as good in financial management will receive an award in the form of an unqualified opinion (WTP). The Principle of Accountability in realizing WTP-based management can be interpreted as an effort to be accountable by creating oversight through the distribution of power in various government institutions so as to reduce the accumulation of power while creating conditions of mutual supervision.